Child Labour in Indonesia: Supply-Side Determinants - Dayang Haszelinna binti Abang Ali; G. Reza Arabsheibani (Economics and Finance in Indonesia, 2016)
This study analyses the determinants of working among 10–17 years’ children and to investigate the presence of Luxury Axiom. Child tends to work as they gets older, has biological ties to the household head and lives in a rural area. The higher levels of household head’s education lead to the children’s been less likely to work. With regard to the Luxury Axiom, household income is negatively impact the work decision. Birth order is positively related to working and the probability of working decreases by the presence of employed adult. Finally, the impact of the child’s activities varies by provinces. AbstrakKajian ini menganalisis faktor-faktor penentu bekerja di kalangan anak-anak yang berusia 10–17 tahun dan untuk menyelidiki keberadaan Luxury Axiom. Anak-anak cenderung untuk bekerja seiring dengan bertambahnya usia mereka, adanya hubungan biologis dengan kepala rumah tangga, dan tempat tinggal mereka di pedesaan. Selain itu, semakin tingginya tingkat pendidikan kepala rumah tangga mendorong ke arah pengurangan kecenderungan anak-anak untuk bekerja. Terkait dengan Luxury Axiom, pendapatan rumah tangga memiliki dampak negatif terhadap keputusan untuk bekerja dan kemungkinan untuk bekerja menurun seiring dengan adanya orang dewasa yang bekerja. Terakhir, besarnya dampak aktivitas anak bervariasi adalah berdasarkan daerah.Kata kunci: Pekerja Anak; Modal Manusia; Lapangan KerjaJEL classifications: J13; J21; O15